A High Efficacy Self‐Charging MoSe2 Solid‐State Supercapacitor Using Electrospun Nanofibrous Piezoelectric Separator with Ionogel Electrolyte. Issue 12 (7th March 2018) - Pazhamalai, Parthiban; Krishnamoorthy, Karthikeyan; Mariappan, Vimal Kumar; Sahoo, Surjit; Manoharan, Sindhuja; Kim, Sang‐Jae
Abstract: Self‐charging supercapacitor power cell (SCSPC) received much attention for harvesting and storing energy in an integrated device, which paves the way for developing maintenance free autonomous power systems for various electronic devices. In this work, a new type of SCSPC device is fabricated comprising 2D molybdenum di‐selenide (MoSe2 ) as an energy storing electrode with polyvinylidene fluoride‐co‐hexafluoropropylene/tetraethylammonium tetrafluoroborate (PVDF‐co‐HFP/TEABF4 ) ion gelled polyvinylidene fluoride/sodium niobate (PVDF/NaNbO3 ) as the piezopolymer electrolyte. The fabricated SCSPC delivers a specific capacitance of 18.93 mF cm −2 with a specific energy of 37.90 mJ cm −2 at a specific power density of 268.91 µW cm −2 obtained at a constant discharge current of 0.5 mA. The MoSe2 SCSPC device can be self‐charged with the aid of mechanical deformation induced using the applied compressive force, thus making it harvest and store energy. The MoSe2 SCSPC device can be charged up to a maximum of 708 mV under a compressive force of 30 N in 100 s, and the mechanism of charge‐storage is discussed in detail. The experimental findings of this work demonstrate the high efficiency of the fabricated MoSe2 SCSPC device, which can provide new insights for developing sustainable power sources for the next generation wearable electronic applications. Abstract : A self‐charging solid‐state supercapacitor comprising 2D MoSe2 nanosheets as the energy storage electrode material and the ionogelled electrospun PVDF/NaNbO3 nanofibrous piezoseparator as the energy harvester source shows excellent self‐charging performance of the self‐charging supercapacitor power cell (SCSPC) device under a compressive force, ensuring the use of the fabricated SCSPC device toward the development of next‐generation integrated energy‐conversion and storage devices.